Effects of ventricular rate and regularity on the velocity and magnitude of left atrial appendage flow in atrial fibrillation. (13th May 2005) - Obel, O A; Luddington, L; Maarouf, N; Aytemir, K; Ekwall, C; Malik, M; Camm, A J
Abstract : Objective: To prospectively determine whether ventricular rate and regularity are significant determinants of the velocity and magnitude of left atrial appendage (LAA) flow. Design and patients: 12 patients with atrial fibrillation (AF), high degree atrioventricular block, and indwelling permanent pacemakers were studied. Setting: Cardiology department of a tertiary referral centre. Interventions: Pacing was triggered by an external programmable transcutaneous device. Patients were paced at 60, 120, and 150 beats/min in both regular and irregular rhythm. LAA flow velocity and magnitude were assessed with transoesophageal Doppler echocardiography. Main outcome measures: Peak and mean LAA inflow and outflow velocity, and time-velocity interval (TVI) of LAA flow. Results: Increasing ventricular rate was associated with significantly lower peak inflow (p < 0.01), peak outflow (p < 0.05), mean inflow (p < 0.01), and mean outflow (p < 0.05) velocities and with a lower TVI of LAA filling and emptying velocities (p < 0.01). This effect was noted at rates of 60 beats/min compared with both 120 and 150 beats/min. At a pacing rate of 120 beats/min there was a significantly higher total TVI when pacing at a regular than at an irregular rhythm (40.16 (14.6) cm v 30.74 (10.9) cm, p < 0.05). Conclusions: In this study, LAA filling velocities in patients in AF were significantly influenced by paced ventricular rate and to a much lesser extent ventricular rhythm. These results suggest that rapid ventricular rates may predispose to stasis in the LAA in AF.